Aktivitas Antioksidan Ekstrak Bubuk Kunyit (Curcuma domestica Val.) - Suhendra, Lutfi (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 2 No 2 (2017), 2018)
This study aims to find out the effect of the concentration of solution and drying temperature in the process of turmeric extraction and to find out the same for producing extract with optimal rendemen and antioxidant activity. The experiment used completely random design and the factorial pattern with the first factor being the solution concentration which consisted of 6 levels, that is, in the concentration of 0%, 30%, 50%, 70%, and 90%. The second factor was the drying temperature which consisted of three levels, they are: 40 o C, 50 o C, and 60 o C with two time repetition. In the examination of the antioxidant activity of turmeric extract, the following tests were done: total phenol (Julkunen-Tito method), the ability of capturing free radical diphenylpikrihidrazil (DPPH), ferry thiosianat method (FTC), and thobarbituric acid method (TBA). The results showed that the concentration of solution and drying temperature affects all parameters under observation, except for the rendemen that is not affected by solution concentration, and there was interaction of treatment in all the parameters observed. Test of FTC and TBA showed that there was antioxidant activity in the turmeric extract where it was able to inhibit the formation of peroxide and malonaldehyde in the oxidization reaction of fatty acid. The turmeric extract with the optimal antioxidant activity was obtained at the treatment of concentration 50% at the temperature of 60 o C with the rendemen value of 7.92%, the total amount of phenol 2.82% and the value of DPPH of 1.13%.